Pendidikan Luqman al-Hakim : kajian ayat nasihat dan bimbingan surah Luqman - Azawiah, Abdullah (2017)
Luqman Al-Hakim education is one of the educational methods written in the Quran. The success and effectiveness of a learning process have high dependency on the educators. But the fact that the teaching profession has become a stepping stone to get a job, which then led to the lack of interest in teaching and unserious in carrying out the task. Therefore, this study was conducted to identify the personal and leaderships characteristics of Luqman al-Hakim one of the educators who has been mentioned in the Quran. In the meantime, this study examines the lessons and guidance from the verses of Surah Luqman by following the mufasirin that can be used as a guide to the educators. The study also analyzed on Luqman’s lesson from the aspect of faith, tarbiyah, social and moral to form a real personality of an educator. The data was collected through document review analysis using content analysis through inductive and deductive processes. The study found that the verses in Surah Luqman presented personal characteristics of an ideal educator. Among them are trusts, always feel grateful, leave unbeneficial things, teach directly and indirectly through actions, always be wise, enjoy into goodness and forbid evils. All these features must be practiced by educators to achieve the goals of education